Painted Gallo-Roman Figurines in Vendeuil-Caply - Adrien Bossard (Les Carnets de l’ACoSt)
In 2013, an archaelogical team exploring the site of Vendeuil-Caply in northern France brought to light a new corpus of Gallo-Roman terracotta figurines. The particular importance of this corpus lies in the preservation of pigments that decorated the surface of these figurines. From the 19th century onwards, the generic term that has been used to refer to this kind of Gallo-Roman production has been “white-clay,” most often associated with the Allier region of central France. This term arose from the stark, white color of the fabric. Consequently, archaeologists were quite surprised to find not only color on the figurines, but also repetitive patterns, such as feathers, or details of clothing.